1996
DOI: 10.1159/000134354
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase I transcription factor UBF and rDNA are located at the same major sites in both interphase and mitotic pig embryonic kidney (PK) cells

Abstract: Indirect immunolabeling with anti-UBF antibodies, in situ hybridization with an rDNA probe, and confocal scanning laser microscopy were used to study nucleolar organizer regions (NORs) during the cell cycle in pig embryonic kidney (PK) cells. The chromosomal distribution of the polymerase I transcription factor UBF and rDNA was compared with the number of silver-stained NORs (Ag-NORs) present and nucleolar size. It was shown, both at interphase and mitosis, that the majority of UBF and rDNA signals were locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Although secondary NORs in Moroccan specimens were comparatively as active as primary ones, the size of the nucleoli yielded was rather different, the primary NORs yielding large nucleoli and the secondary NORs very small ones. This is consistent with the existence of a relationship between the number of rRNA genes in a NOR and the amount of rRNA synthesized and, consequently, the nucleolus size (De Capoa et al 1988, Shubert and Ktinzel 1990, Zatsepina et al 1996.…”
Section: Discussionsupporting
confidence: 75%
“…Although secondary NORs in Moroccan specimens were comparatively as active as primary ones, the size of the nucleoli yielded was rather different, the primary NORs yielding large nucleoli and the secondary NORs very small ones. This is consistent with the existence of a relationship between the number of rRNA genes in a NOR and the amount of rRNA synthesized and, consequently, the nucleolus size (De Capoa et al 1988, Shubert and Ktinzel 1990, Zatsepina et al 1996.…”
Section: Discussionsupporting
confidence: 75%
“…Each transcription factor (UBF and others) may bind randomly to ribosomal cistrons in all clusters, or once the first factors are bound the others may bind in a cooperative manner (Moss 1983;Zurita et al 1998;for review see Jacob 1995). A correlation between the size of AgNORs and the amount of the transcription factor UBF has been shown in several studies (Roussel and Hernandez-Verdun 1994;Zatsepina et al 1996), and stick-like and pair NOR structures are also observed by immunostaining for UBF (Héliot et al 1997). RPI is also associated with rDNA in mitotic NORs (Scheer and Rose 1984;Zatsepina et al 1996) and is stalled after the transcription of a few hundred bases (Weisenberger and Scheer 1995).…”
Section: Discussionmentioning
confidence: 81%
“…A correlation between the size of AgNORs and the amount of the transcription factor UBF has been shown in several studies (Roussel and Hernandez-Verdun 1994;Zatsepina et al 1996), and stick-like and pair NOR structures are also observed by immunostaining for UBF (Héliot et al 1997). RPI is also associated with rDNA in mitotic NORs (Scheer and Rose 1984;Zatsepina et al 1996) and is stalled after the transcription of a few hundred bases (Weisenberger and Scheer 1995). These data suggest that assembled transcription complexes inherited from the previous interphase may determine the pattern of an AgNOR at the beginning of the next cell cycle (Ferraro et al 1981).…”
Section: Discussionmentioning
confidence: 86%
“…44,51 Importantly, the observation that UBF remains associated with the rRNA genes throughout mitosis even when rDNA transcription is shut down provides a mechanistic explanation for why active NORs remain undercondensed during mitosis and have a distinct chromatin structure that is evident as secondary constriction on metaphase chromosomes. [51][52][53]…”
Section: Ubf Functions In Maintaining Undercondensed R-chromatin Of Amentioning
confidence: 99%